Modulation of the host lipid landscape to promote RNA virus replication: the picornavirus encephalomyocarditis virus converges on the pathway used by Hepatitis C virus - Dorobantu, Cristina M.; Albulescu, Lucian; Harak, Christian; Feng, Qian; Kampen, Mirjam van; Strating, Jeroen R. P. M.; Gorbalenya, Alexander E.; Lohmann, Volker; Schaar, Hilde M. van der; Kuppeveld, Frank J. M. van (PLoS pathogens, 2015)
Cardioviruses, including encephalomyocarditis virus (EMCV) and the human Saffold virus, are small non-enveloped viruses belonging to the Picornaviridae, a large family of positive-sense RNA [(+)RNA] viruses. All (+)RNA viruses remodel intracellular membranes into unique structures for viral genome replication. Accumulating evidence suggests that picornaviruses from different genera use different strategies to generate viral replication organelles (ROs). For instance, enteroviruses (e.g. poliovirus, coxsackievirus, rhinovirus) rely on the Golgi-localized phosphatidylinositol 4-kinase III beta (PI4KB), while cardioviruses replicate independently of the kinase. By which mechanisms cardioviruses develop their ROs is currently unknown. Here we show that cardioviruses manipulate another PI4K, namely the ER-localized phosphatidylinositol 4-kinase III alpha (PI4KA), to generate PI4P-enriched ROs. By siRNA-mediated knockdown and pharmacological inhibition, we demonstrate that PI4KA is an essential host factor for EMCV genome replication. We reveal that the EMCV nonstructural protein 3A interacts with and is responsible for PI4KA recruitment to viral ROs. The ensuing phosphatidylinositol 4-phosphate (PI4P) proved important for the recruitment of oxysterol-binding protein (OSBP), which delivers cholesterol to EMCV ROs in a PI4P-dependent manner. PI4P lipids and cholesterol are shown to be required for the global organization of the ROs and for viral genome replication. Consistently, inhibition of OSBP expression or function efficiently blocked EMCV RNA replication. In conclusion, we describe for the first time a cellular pathway involved in the biogenesis of cardiovirus ROs. Remarkably, the same pathway was reported to promote formation of the replication sites of hepatitis C virus, a member of the Flaviviridae family, but not other picornaviruses or flaviviruses. Thus, our results highlight the convergent recruitment by distantly related (+)RNA viruses of a host lipid-modifying pathway underlying formation of viral replication sites.
Gesehen am 22.06.2020